Differences of the 6N and 6J Substrains of C57BL/6 Mice in the Development of Experimental Autoimmune Encephalomyelitis - Ana Isabel Álvarez‐López; Eduardo Ponce‐España; Ivan Cruz‐Chamorro; Guillermo Santos‐Sánchez; Ignacio Bejarano; Nuria Álvarez‐Sánchez; Patricia Judith Lardone; Antonio Carrillo‐Vico (MedComm)
ABSTRACT Multiple sclerosis (MS) is an autoimmune disease causing neuroinflammation and demyelination in the central nervous system (CNS). It is traditionally considered CD4+ T cell‐mediated, but several immune cells, such as CD8+ cells, B cells, macrophages, and dendritic cells (DC) also contribute to the pathogenesis. Moreover, altered gut microbiota, including changes in specific genera, has been observed in MS patients. The murine model of MS, experimental autoimmune encephalomyelitis (EAE), is mainly carried out in C57BL/6 mice. Historically, N and J substrains have been used interchangeably, and many laboratories are not even aware of which strain they are using. Therefore, the objective of this study was to evaluate the differences between the 6J and 6N substrains subjected to myelin oligodendrocyte glycoprotein (MOG35–55) induced EAE in the composition of neuroinflammatory cells and microbiota. 6J substrain presented a more severe EAE than the 6N substrain, accompanied by an increase in the frequency of macrophages, CD8+, and B cells within the infiltrated immune cells compartment. In addition, 6J animals have a higher proinflammatory profile and a lower anti‐inflammatory profile compared with the 6N substrain. Consistent with this, the differences observed in the basal microbial taxa between both substrains support the differences observed in the immunological response.